2021
DOI: 10.1111/jcmm.16499
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of FoxO3a in the regulation of trophoblast development and pregnancy complications

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Namely, multiple families bore motifs for key factors involved in the maintenance of the stem cell state, such as ELF5, GATA3, TFAP2C, TP63 and TEAD4 (Figure 2A; Supplementary Figure 2A). Additional transcription factors with known roles in placental development and/or physiology included JUN/FOS (He et al, 2019; Kubota et al, 2015), PPARG/RXRA (Kadam et al, 2015), and FOXO3 (Chen et al, 2021). To validate the binding of some of these transcription factors to hTSC-active TEs, we performed CUT&Tag or CUT&RUN (Skene and Henikoff, 2017) for JUN, JUND, GATA3, TEAD4 and TFAP2C (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, multiple families bore motifs for key factors involved in the maintenance of the stem cell state, such as ELF5, GATA3, TFAP2C, TP63 and TEAD4 (Figure 2A; Supplementary Figure 2A). Additional transcription factors with known roles in placental development and/or physiology included JUN/FOS (He et al, 2019; Kubota et al, 2015), PPARG/RXRA (Kadam et al, 2015), and FOXO3 (Chen et al, 2021). To validate the binding of some of these transcription factors to hTSC-active TEs, we performed CUT&Tag or CUT&RUN (Skene and Henikoff, 2017) for JUN, JUND, GATA3, TEAD4 and TFAP2C (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Namely, multiple families bore motifs for key factors involved in the maintenance of the stem cell state, such as ELF5, GATA3, TFAP2C, TP63 and TEAD4 (Figure 2A; Supplementary Figure 2A). Additional transcription factors with known roles in placental development and/or physiology included JUN/FOS 27,28 , PPARG/RXRA 29 , and FOXO3 30 . Most of these motifs were also present in elements negative for H3K27ac (Supplementary Figure 2B), suggesting that there are additional genetic or epigenetic determinants of their activity, similar to what we had observed in mouse TSCs 18 .…”
Section: Htsc-active Ervs Bind Key Placenta-associated Transcription ...mentioning
confidence: 99%
“…Recently, several researchers reported that tryptophan (one of the three aromatic amino acids) had been involved in migration and invasion via cyclooxygenase-2 (COX-2, also named PTGS2) and matrix metallopeptidase 9 (MMP9) (Gu et al 2021 ; Liu et al 2020 ). Our previous RNA-seq study consistently demonstrated that COX-2 and MMP9 were decreased after FoxO3a depletion (Chen et al 2021 ), and the expression of these two genes is negatively correlated with all three aromatic amino acids acid concentrations under FoxO3a knockdown condition (Fig. 6 B).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that DNA methylation in the enhancer regions of SPATS2L resulted in decreased protein expression in chorionic villi. The human extravillous trophoblast cell line HTR8/SVneo is widely used as a model for first trimester extravillous trophoblasts invasion and migration 28 30 . Our functional study using this cell line revealed that SPATS2L is involved in its migration and invasion.…”
Section: Discussionmentioning
confidence: 99%